Catastrophic failure of ceramic-on-ceramic total hip arthroplasty presenting as squeaking hip - Malem, David (BMJ Publishing Group, 2013)
A 68-year-old woman with osteoarthritis had a ceramic-on-ceramic left total hip arthroplasty, including ceramic femoral head and acetabular liner. At 5 years after surgery, the patient developed onset of a very loud squeaking noise, which could be heard 25 m from her, associated with limited hip movement. Findings at revision surgery included a broken ceramic femoral head component, complete wear of the ceramic acetabular component, and black wear debris. Squeaking hip after ceramic-on-ceramic total hip arthroplasty may be associated with catastrophic failure of the arthroplasty components.